PENILAIAN RISIKO KESELAMATAN DAN KESEHATAN KERJA PADA UNIT LABORATORIUM TEKNIK SEPEDA MOTOR SMKN 2 KOTA PALEMBANG - , DESHEILA ANDARINI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background:, There is a work practice programme that can cause accidents in the Vocational School. The tendency of vocational education and technology today has shifted into a small factory in a school environment for students to practice. SMKN 2 Palembang is a school with Community College model which is proclaimed as one of the excellent school and have new equipment assistance in Lab TSM and TPM . Risk assessment of occupational health and safety is never conducted and they have no system in managing hazard in lab unit which could potentially cause an accident in the work, so itâs important for conducting risk assessments. Objective: To perform an occupational health and safety risk assessments in TSM and TPM unit of SMKN 2 Palembang Method: This research was a qualitative study with semi quantitative risk assessment analysis and research design in the form of case studies ( case study ). Research subjects were three key informant and five informant . Information obtained by observation, literature, in-depth interviews, walk- through survey, risk management worksheet, and hazard checklist. Result: The result showed that hazard identification and risk assessment in SMKN 2 Palembang were divided on Motorcycles Technical Unit and Machine Techniques Unit. Some of identified hazard were bruised, fire, noise, CO, heat , slip, electric shock, dust and smoke, struck down tool, fatigue, weight lifting, human error , asbestos powder, used oil, chlorinated hydrocarbon and H2SO4. Conclusion:, There were 41 hazard from hazard identification. Risk assessment showed that the most risk was in acceptable category, and the highest risk was in significant category. Risk evaluation showed that noise measurement result was above threshold value. Control activities for the highest risk were by routine supervision, safety talk, and personal protective equipment for teacher and student.